HÏSTORICAL-COMPARÀTÏVE ANALYSIS OF INTELLIGENCE-SECURITY COMMUNITIES OF ALBANIA AND ROMANIA IN THE ERA OF COMMUNISM (Annual of the Faculty of Philosophy in Skopje, 2008)
The purpose of this study is to compose comparative analysis of two identical intelligence-security systems that were functioning in Albania and Romania in the era of communism. In the focus of this research are two most malicious services, which operated as classical secret political police, services that used identical crude methods-Sigurimi and Securitate.Both services represent blast fist of the most repressive totalitarian communist regimes in the role of realization ofpolitics of both greatest and malicious communist dictators (out of borders of SSSR)-Enver Hoga and Nikolae Causesku.Their politics of creation of “internal enemy ” and uncompromised struggle with the same, from their domination, made Sigurimi and Securitate to transform in “state in state”, to become wild and to realize unseen torture upon own nation. With their uncontrolled policies and politics power they made from their states to create the largest “camps” in the world. Every similarity for their end also tells for match of there “communist dictate”, but on the confraiy, for theirs hate from own people.Every similarity with Albanian security model in the time of ruling of Albanian and Romanian communist dictator is “random ”, as random as is identical their end and ending of their secret polices.
Keywords: SECRET POLICE; COMMUNIST SYSTEM; INTELLIGENCE- SECURITY COMMUNITY; TOTALITÄREM; REPRESSIVE APPARATUS